Staphylococcus aureus small colony variants show common metabolic features in central metabolism irrespective of the underlying auxotrophism - Kriegeskorte, André; Grubmüller, Stephanie; Huber, Claudia; Kahl, Barbara C.; von Eiff, Christof; Proctor, Richard A.; Peters, Georg; Eisenreich, Wolfgang; Becker, Karsten (Frontiers in Cellular and Infection Microbiology, 2014)
In addition to the classical phenotype, Staphylococcus aureus may exhibit the small colony-variant (SCV) phenotype, which has been associated with chronic, persistent and/or relapsing infections. SCVs are characterized by common phenotypic features such as slow growth, altered susceptibility to antibiotic agents and pathogenic traits based on increased internalization and intracellular persistence. They show frequently auxotrophies mainly based on two different mechanisms: (i) deficiencies in electron transport as shown for menadione- and/or hemin-auxotrophs and (ii) thymidylate biosynthetic-defective SCVs. To get a comprehensive overview of the metabolic differences between both phenotypes, we compared sets of clinically derived menadione-, hemin- and thymidine-auxotrophic SCVs and stable site directed mutants exhibiting the SCV phenotype with their corresponding isogenic parental strains displaying the normal phenotype. Isotopologue profiling and transcriptional analysis of central genes involved in carbon metabolism, revealed large differences between both phenotypes. Labeling experiments with [U-13C6]glucose showed reduced 13C incorporation into aspartate and glutamate from all SCVs irrespective of the underlying auxotrophism. More specifically, these SCVs showed decreased fractions of 13C2-aspartate and glutamate; 13C3-glutamate was not detected at all in the SCVs. In comparison to the patterns in the corresponding experiment with the classical S. aureus phenotype, this indicated a reduced carbon flux via the citric acid cycle in all SCV phenotypes. Indeed, the aconitase-encoding gene (acnA) was found down-regulated in all SCV phenotypes under study. In conclusion, all SCV phenotypes including clinical isolates and site-directed mutants displaying the SCV phenotype were characterized by down-regulation of citric acid cycle activity. The common metabolic features in central carbon metabolism found in all SCVs may explain similar characteristics of the S. aureus SCVs irrespective of their auxotrophism as well as the specific genetic and/or regulatory backgrounds.